Coexistence of IMT-Advanced Systems for Spectrum Sharing with FSS Receivers in C-Band and Extended C-Band - Abdulrazak, Lway Faisal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides information regarding spectrum sharing between wireless systems, motivated by emerging new technologies.  Readers will benefit from information about how to conduct research on the interference mitigation between IMT-Advanced and FSS. The author presents a deterministic analysis for interference to noise ratio (I/N), adjacent channel interference ratio (ACIR), field strength, and path loss propagation, in order to determine the separation distances in the co-channel interference (CCI) and adjacent channel Interference (ACI) scenarios. An analytical model is discussed, for the shielding mitigation technique based on the deterministic analysis of the propagation model. The shielding technique has been developed based on test bed measurements for evaluating the attenuation of the proposed materials. Matlab™ and Transfinite Visualyse Pro™ have been used as simulation tools for the verification of the obtained results, whereas the IMT-Advanced parameters have been represented by Worldwide Interoperability for Microwave Access (WiMAX) 802.16e.
Chapter 1.Introduction -- Chapter 2.Literature Review -- Chapter 3. Interference Assessment Methodology -- Chapter 4.FSS Shielding and Antenna Discrimination as an Interference Mitigation Techniques -- Chapter 5. I-Music Algorithm and Fixed Nulls Insertion -- Chapter 6.Conclusion and Future Work.
Keywords: Signal processing; Electronic circuits; Electronics; Signal, Speech and Image Processing; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation